Collaborative writing groups for academic publishing : the 3C and 4P way - Semon, Sarah; Catania, Nicholas; Lane, Danielle; Hinton, Jessica (Emerald Publishing Limited, 2024)
Recognizing the increasing workload placed on academics amidst a highly competitive publishing landscape, Collaborative Writing Groups for Academic Publishing: The 3C and 4P Way helps aspiring researchers establish hyper-productive virtual writing groups to build personal confidence and professional relationships, develop their academic writing skillsets, and further their careers. Drawing on their own experiences, including their motivations and career paths, the authors offer practical guidance for establishing collaborative writing groups using the 3Cs (Common Focus, Commitments, and Communication) and the 4Ps (Priorities, Plans, Protecting Deadlines, and Positive Reinforcement). Walking readers through a series of developmental phases, the authors also provide a thorough discussion of useful analogue and digital tools to support groups in an ongoing cycle of goal setting, progress monitoring, and success celebrating. Encouraging a sense of community building and collaboration, which counteracts the isolation and competition that often plagues the academic sphere, chapters also explore the less measurable aspects of group collaboration: trust, respect, follow through, flexibility, the ability to discuss critically without fear, and a willingness to stick with their efforts even if results take a few tries. Grounded in the practical implementation of the C3P4 process, this timely work acts as an essential manual for aspiring academics to achieve the ultimate collaborative workflow, benefitting both researchers and those their research will impact.
Keywords: Authorship -- Collaboration.; Scholarly publishing.; Academic writing.; Education -- Collaborative & Team Teaching.; Writing and editing guides.; Teaching skills and techniques.; elektronické knihy; electronic books